NEW OPPORTUNITIES OF TREATMENT OF DIFFERENT TYPES OF JUVENILE ARTHRITIS WITH MONOCLONAL ANTIBODIES TO THE INTERLEUKIN 6 RECEPTOR - E.I. Alexeeva; R.V. Denisova; S.I. Valieva; T.M. Bzarova; A.O. Lisitsyn ("Paediatrician" Publishers LLC, 2010)
The article observes the data on the role of interleukin (IL) 6 in pathogenesis of rheumatoid arthritis and treatment of rheumatoid arthritis and different types of juvenile arthritis with blocker IL 6 receptor (tocilizumab). The data on multicenter open-labeled and double-blinded randomized studies on effectiveness and safety of tocilizumab are reviewed. The results of studies showed high effectiveness and safety of tocilizumab in treatment of rheumatoid arthritis and juvenile arthritis.  Key words: children, rheumatoid arthritis, juvenile arthritis, interleukin 6, treatment, tocilizumab. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):52-61)